ASYMPTOTIC NORMALITY OF A KERNEL-TYPE ESTIMATOR FOR THE INTENSITY OF A PERIODIC POISSON PROCESS - MANGKU, I W. (MILANG Journal of Mathematics and Its Applications, 2006)
In this paper we prove asymptotic normality of a kernel type estimator for the intensity of a periodic Poisson process. This paper is a continuation of [10]. As in [10], we consider the situation when the period is known in order to be able to present simple proofs of the results.1991 Mathematics Subject Classiﬁcation: 60G55, 62G05, 62G20.